Cystic Fibrosis in the Light of New Research - Wat, Dennis (IntechOpen, 2015)
Cystic Fibrosis in the Light of New Research provides the latest research and clinical evidence that will be useful for clinicians, scientists and researchers to further their knowledge around this fascinating condition. The authors have brought along their expertise and wealth of knowledge to produce this book, including the basic science that underlies the disease, the burden of bacterial and viral infections, immunologic aspects of CF, a variety of clinical measurements to predict prognosis and novel therapies including gene therapy. This book will be invaluable and entertaining for anyone who is involved in the care of patients with cystic fibrosis.